2020
DOI: 10.3390/molecules25040973
|View full text |Cite
|
Sign up to set email alerts
|

Higher Levels of Low Molecular Weight Sulfur Compounds and Homocysteine Thiolactone in the Urine of Autistic Children

Abstract: In this study, the levels of concentration of homocysteine thiolactone (HTL), cysteine (Cys), and cysteinylglycine (CysGly) in the urine of autistic and non-autistic children were investigated and compared. HTL has never been analyzed in autistic children. The levels of low molecular weight sulfur compounds in the urine of both groups were determined by validated methods based on high-performance liquid chromatography with spectrofluorometric and diode-array detectors. The statistical data show a significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Potential explanations may be due to sex-related differences in the prevalence and effects of polymorphic gene variants [55]. Accordingly, anomalous transsulfuration pathway and dysregulated folate or Hcy metabolism may lead to aberrant redox homeostasis and neurodegeneration, and in turn, increased ASD susceptibility [56][57][58]. Several studies have indeed reported a correlation between high Hcy and low folate, vitamin B6, and B12 levels with ASD and severity [58,59].…”
Section: One-carbon Metabolism Pathwaymentioning
confidence: 99%
“…Potential explanations may be due to sex-related differences in the prevalence and effects of polymorphic gene variants [55]. Accordingly, anomalous transsulfuration pathway and dysregulated folate or Hcy metabolism may lead to aberrant redox homeostasis and neurodegeneration, and in turn, increased ASD susceptibility [56][57][58]. Several studies have indeed reported a correlation between high Hcy and low folate, vitamin B6, and B12 levels with ASD and severity [58,59].…”
Section: One-carbon Metabolism Pathwaymentioning
confidence: 99%
“…A point mutation in the gene encoding MTHFR , which is located on chromosome 1p36.3, is associated with several malignancies, including colon cancer, gastric cancer, lung cancer, esophageal squamous cell carcinoma, breast cancer, and gynecological cancer ( 11 18 ). MTHFR is a critical enzyme involved in the folate metabolism pathway and DNA methylation and synthesis ( 19 ). The MTHFR C677T, a cytosine (C) to a thymine (T) substitution at position 677, which changes an alanine to a valine, leads to impaired folate binding and reduced MTHFR activity ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Homocysteine thiolactone (HTL) is a well-known modifying factor of proteins, and its role in the pathogenesis of different diseases has started to be recognized [ 1 , 2 , 3 , 4 ]. HTL is a chemically reactive metabolite generated by methionyl-tRNA synthetase and cleared by the kidney [ 5 ].…”
Section: Introductionmentioning
confidence: 99%